"Who made it to the pros?" A 5-year longitudinal study on the role of achievement motivation in football - Zuber, C.; Sieghartsleitner, R.; Zibung, M.; Conzelmann, A. (International Journal of Sport Psychology, 2022)
The importance of achievement motivation for the development of athletic performance has been widely acknowledged. However, evidence on the relation of motivational characteristics from adolescence to elite performance level is still rare. The aim of the present study was to examine whether motivational patterns of U14 football players were associated with successful football performance at the U19 age group. A sample of 94 elite youth male football players (MAge = 13.31, SD = 0.29), completed a series of achievement motivation questionnaires. Five years later, their respective football performance level was assessed. Players with a highly intrinsically achievement-oriented profile displayed a higher likelihood of reaching professional level (OR = 3.5), which supports the importance of motivational characteristics for the development of athletic performance over a mid-term prognosis period.